An Econometric Study of Palm Oil Import Demand in the Middle East and North African Countries - Abdeghameed, Amna Awad (2005)
With vegetable oils supplies at record levels, increased emphasis is being placed on finding new and growing markets for different oils. The Middle East and North Africa region (MENA) is one of such emerging markets for palm oil and its products. Strong consumption growth for vegetable oils in general, and palm oil products in particular, coupled with limited vegetable oils production capabilities in the region, have been behind the increase in trade. Further growth is anticipated in large part due to a strong regional GDP forecast. Palm oil has the opportunity to be a prime beneficiary of this growth in trade, due to its export competitiveness in the global market of fats and oils. The objectives of this study are; firstly to analyse the palm oil import demand in representative MENA countries, namely Algeria, Egypt, Iran, Jordan, Libya, Morocco, Saudi Arabia, Sudan, Syria, and Turkey, over a period of time; and secondly, to identify the prospects of expanding its market in the MENA regon. Ten single equation models are specified, following a general to specific approach. to represent palm oil import demand functions in these countries. The models have been estimated using multivariate cointegration and ECM methods for the analysis through utilizing the ARDL technique. The findings of the study show that the palm oil price variable emerged to be a significant determinant of palm oil demand across the ten models. Soybean oil proved to be an important substitute for palm oil in Algeria, Egypt, Iran, Jordan, Morocco and Turkey. The major substitute oil for palm oil in Saudi Arabia and Libya is corn oil, while rapeseed oil and sunflower seed oil came out to be important substitutes for it in Sudan and Syria respectively. The prices of substitute oils in almost all countries have been found to play an important role in shaping the palm oil demand. Palm oil demand in all countries turned to be significantly dependent on income. The remarkably high palm oil discount was an important factor in raising the Turkish demand for palm oil. The results suggest that the sharp increase in world petroleum prices in 1970s contributed significantly to the palm oil import demand in Saudi Arabia.The anti-palm oil campaign came out to be an important factor that negatively affected the palm oil import demand in Algeria and Iran. The Malaysian market promotion effort proved to have a great influence in expanding the demand for palm oil in Egypt. The Gulf war crisis and trade sanctions on Iraq expanded the market of palm oil in Jordan, whereas the trade embargo on Libya suppressed the demand. Exchange rate also proved to be an important determining factor for shaping Libyan import demand for palm oil. Demand elasticities with respect to own price, substitute price and income came out to be very high indicating its high responsiveness to changes in these variables and implying the importance of considering them in the process of formulating the marketing policies. f'W'UfJAM SULTAN &DW S A W HWftsTl WiU MAlAYSlA Finally, projections for palm oil import demand revealed that import demand is expected to increase in all the countries under consideration, with variations in the magnitude of expansion among them, indicating the good potentiality of this market for absorbing more palm oil.